Market-Orientation and Its Impact on the Performance of Asia Insurance Company in Kerman Province - Jandaghi, Gholamreza; ., Ali Mokhles; ., Hassan Kharazi (Journal of Economics and Behavioral Studies, 2011)
The key of successes by service providers can be found in their market-orientation. These are organizations which pay more attention to customers and rivals and attempt to provide services with the highest quality. Present paper has studied experimentally the relationship between market-orientation and performance of agencies and brokers of Asia Insurance Company in Kerman province. Here, the scale of market-orientation in service sector is applied. The methodology is field study and the tool to gather information is questionnaire. Factors analysis shows that there are four hidden aspects in the title of market-orientation: customer-orientation, rival-orientation, organizational responsiveness, propensity to customer satisfaction. Findings suggest that customer–orientation and propensity to customer satisfaction have remarkable impacts on performance relative to other aspects. Rival-orientation has lower impact on performance and organizational responsive has an inconsistency relationship with performance.